Aktualisasi Misi dan Pemuridan Guru Pendidikan Agama Kristen dalam Era Disrupsi - Tenny Tenny; Yonatan Alex Arifianto (Didache: Journal of Christian Education, 2021)
Christian Religious Education teachers play a significant role in determining the spiritual increase of students. However, there are still many who do not realize and respond to the current state of disruption. They are less focused on students and prioritize cognitive only so that efforts to fulfill the Great Commission of the Lord Jesus are less significant results or developments in this era of disruption. To further discuss the actualization of the mission and discipleship of Christian Religious Education teachers in the era of disruption, the author uses the library research method in this discussion. The role of Christian religious education teachers in Mission and Discipleship must be the main goal through education that prioritizes and cares for the generation of the era of disruption. By equipping the understanding of God's Great Commission in mission education for Christian Religious Education teachers, they can be encouraged to improve teaching and learning methods. The purpose of this discussion is that the actualization of the mission and discipleship of Christian Religious Education teachers in an era of disruption can bring growth and development for the progress of God's church to be filled with true disciples of Christ.